THE RELATIONSHIP BETWEEN HUSBAND SUPPORT AND MIDWIFE ROLE WITH POST PARTUM CONTRACEPTION IN KONAWE KEPULAUAN DISTRICT: POST PARTUM CONTRACEPTION - Dian Wulandari; Sunarsih Sunarsih; Akbar Torontju (STIKes Mandala Waluya Kendari, 2021)
Background: Postpartum contraceptive coverage in Konawe Kepulauan Regency in 2018, through data obtained at the Konawe Kepualaun District Health Office, Southeast Sulawesi Province as much as 8.4% and data in 2019 decreased to 1.26%. Methods:This quantitative research is observational with a cross sectional study design. The population in this study was 96 people with the determination of the sample using stratified cluster sampling, totaling 77 all post-partum mothers in the working area of the health centre in Konawe Kepulauan Regency. Results:The significance value (p) value of husband support and the role of midwife is 0.000 which means that p <0.05 so that Ha is accepted and Ho is rejected, which means that there is a significant correlation or relationship between husband's support and the role of midwives on the use of postpartum contraception. Both have a value of phi C which is 0.100 which meansvery weak relationship. Conclusion: There is a relationship between husband's support and the role of the midwife against the use of postpartum contraceptives in the Konawe Islands district.